Computational transport phenomena of fluid-particle systems - Arastoopour, Hamid; Gidaspow, Dimitri, 1934-; Abbasi, Emadoddin (Springer, 2017)
This book concerns the most up-to-date advances in computational transport phenomena (CTP), an emerging tool for the design of gas-solid processes such as fluidized bed systems. The authors examine recent work in kinetic theory and CTP and illustrate gas-solid processes' many applications in the energy, chemical, pharmaceutical, and food industries. They also discuss the kinetic theory approach in developing constitutive equations for gas-solid flow systems and how it has advanced over the last decade as well as the possibility of obtaining innovative designs for multiphase reactors, such as those needed to capture CO2 from flue gases. Suitable as a concise reference and a textbook supplement for graduate courses, Computational Transport Phenomena of Gas-Solid Systems is ideal for practitioners in industries involved with the design and operation of processes based on fluid/particle mixtures, such as the energy, chemicals, pharmaceuticals, and food processing. Explains how to couple the population balance equation (PBE) with CTP models and use available methods of moments to solve these equations; Addresses modified CTP governing equations and codes that predict the effect of non-homogeneous flow on process design and scale-up; Provides theoretical equations of state and transport properties for each phase of granular flow kinetic theory.
Keywords: Multiphase flow.; Computational fluid dynamics.; Transport theory.; elektronické knihy; electronic books